Faktor-Faktor yang Berhubungan dengan Perilaku Pencegahan Penyakit Hipertensi pada Lansia di Kecamatan Senen Kota Jakarta Pusat Tahun 2025 - Nugraheni, Fitrilia; Widowati, Evi; Rustiana, Eunike Raffi (Lembaga Pengembangan Kinerja Dosen, 2025)
Hypertension is a non-communicable disease with the highest global prevalence, reaching 33.1%, and Indonesia ranks second among countries in the South-East Asia region. In DKI Jakarta, based on the 2023 SKI report, the prevalence of physician-diagnosed hypertension reached 12.6%, the highest recorded in the past 15 years, and hypertension accounted for 52% of non-communicable disease–related deaths in 2024. Central Jakarta has the highest prevalence (12.20%), with Senen District reporting the highest subdistrict prevalence (12.50%), predominantly among older adults. This study aims to analyze factors associated with hypertension prevention behaviors among older adults in Senen District. The study employed an analytic observational design with a cross-sectional approach. The study population consisted of 13,292 older adults, and a total of 106 respondents were selected using Proportionate Stratified Sampling. Primary data were collected through interviews using structured questionnaires. Data were analyzed using chi-square tests and logistic regression. Bivariate analysis demonstrated significant associations between education, knowledge, attitudes, access to healthcare facilities, family support, and support from healthcare workers (p<0.05). Multivariate analysis identified knowledge (OR 10.642), healthcare facilities (OR 5.785), and attitudes (OR 5.101) as variables significantly influencing hypertension prevention behaviors. Knowledge was found to be the dominant variable with the strongest effect. The study recommends strengthening health education and counseling tailored to the educational level of older adults, as well as enhancing continuous support through community health posts (Posyandu) and home visits. Family involvement in supporting preventive practices is also encouraged. Future research is recommended to employ a mixed-methods approach to obtain a more comprehensive understanding of factors influencing hypertension prevention behaviors in older adults.